Bromeliáceas notables de colombia, iii (1945)
Aechmea (Platyaechmea) anómala / Greigia excerta / Guzmania coriostachya / Guzmania cryptantha / Guzmania gloriosa / Pitcairnia alborubra / Pitcairnia bella / Pitcairnia oblanceolata / Pitcairnia Schultzei / Pitcairnia semaphora / Tillandsia chontalensis / Tillandsia disticha / Tillandsia excavata / Tillandsia Funckiana / Tillandsia Gardneri / Tillandsia (Platystachys) mima / Tillandsia rectiflora